"Under the Yoke": The Archaeology of the Ottoman Period in Bulgaria. (30th June 2017) - Petersen, Andrew
Abstract : The aim of this article is to draw attention to the considerable potential for investigating the Ottoman archaeology of Bulgaria and also to consider what research has already been carried out. Because the modern state gained its independence from the Ottomans this period of history is generally regarded in negative terms. The physical evidence of the Ottoman era, in particular mosques and other Muslim religious buildings, were reminders of an alien past and many of them were destroyed or allowed to fall into ruin. Increasing archaeological activity in recent years combined with a more open approach to the Ottoman past have meant that there is now considerable potential for archaeological research of the Ottoman period.